HOW CULTURAL HERITAGE CAN POSITIVE INFLUENCE TOURISM THE MEMORY OF PLACE - Silva Vidal Saraiva, Alexandra Maria Barros Alves Chaves (European Scientific Journal, ESJ, 2015)
The purpose of this article is to show how architects, planners and local authorities can create their own language interpretation and application of formal relations, at the same time; they developed their rehabilitation programs and promotional tourism, which transposes the analysis of the cultural landscape to the formal development of each program unit. The designation of cultural heritage results of the configuration analysis in History, Geography and Architecture in direct relation to the phenomena that arise. And tourism can contribute substantially to the financial maintenance of monuments, and also to help public support created for conservation policies. And all organizations such as World Heritage Cultural Landscape, ICCRDM and ICOMOS, help define the purpose of the question. The heritage depends on a phenomenological and sociological interpretation related then with History of Architecture, with the goal of understanding the cultural heritage. The main conclusion of this article is to emphasize that the factors which will determine the new heritage, and also influence Tourism, are defined by population, lifestyle and economy. Therefore they are important factors to achieve successfully interventions and programs, public or private.